2017
DOI: 10.1002/bjs.10526
|View full text |Cite
|
Sign up to set email alerts
|

Non-technical skills of surgeons and anaesthetists in simulated operating theatre crises

Abstract: A higher level of NTS of surgeons and anaesthetists led to quicker crisis resolution in a simulated operating theatre environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 27 publications
1
39
1
Order By: Relevance
“…This study was conducted using simulated videos of general and cardiothoracic surgery, which, although realistic and standardized, are not real operative events. Recent analyses have demonstrated that NOTSS can predict improved performance in simulated surgical crises and the modality of simulation continues to be of interest for researchers to test patient safety innovations before implementation in the real clinical environment. The videos were scripted to show the full range of behaviours, modelled from clinical events, but a limitation of using a single video per group is that participants may have found it too easy or difficult to rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was conducted using simulated videos of general and cardiothoracic surgery, which, although realistic and standardized, are not real operative events. Recent analyses have demonstrated that NOTSS can predict improved performance in simulated surgical crises and the modality of simulation continues to be of interest for researchers to test patient safety innovations before implementation in the real clinical environment. The videos were scripted to show the full range of behaviours, modelled from clinical events, but a limitation of using a single video per group is that participants may have found it too easy or difficult to rate.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite being the most used tool for assessment of surgeons' non‐technical skills and substantial reliability testing in different contexts around the world, validity evidence for the underpinning skills taxonomy is limited to studies conducted to develop the tool. Two recent studies utilizing NOTSS have demonstrated that the tool can be used by surgical assessors to detect incremental improvements in behaviour, and to predict effective crisis resolution during simulated surgical emergencies. Adapted versions for surgery in different contexts have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Most frequently, two observers collected data (n ¼ 7). [40][41][42]44,48,49,55 Fourteen studies involved an observer with a clinical background, 9,42,[44][45][46]48,50,[52][53][54][55][56][57][58] and eight studies involved a nonclinical observer. 41,42,44,45,[47][48][49][50] Fourteen of the 19 studies reported details of observer training.…”
Section: Non-technical Skills For Surgeonsmentioning
confidence: 99%
“…41,42,44,45,[47][48][49][50] Fourteen of the 19 studies reported details of observer training. 9,41,42,[44][45][46][47][48]50,52,53,56,58 Validity and reliability. Validity for NOTSS was established by 13 studies (nine of which were conducted in a simulation environment).…”
Section: Non-technical Skills For Surgeonsmentioning
confidence: 99%
“…Although action must be taken to educate and if possible rescue poor performers, they may sometimes need to be removed from the clinical frontline—often a difficult and painful process for everyone. Better understanding of appropriate non-technical skills makes such assessment easier, facilitates rescue in many cases,2 and is more overt for all concerned.…”
mentioning
confidence: 99%